2013
DOI: 10.1111/exd.12131
|View full text |Cite
|
Sign up to set email alerts
|

Topical tacrolimus does not negatively impact acute skin wound healing

Abstract: Despite the increasing use of topical tacrolimus, there is little information about its effect on skin wound healing. To determine effects on acute cutaneous wound healing, two fullthickness skin wounds were imparted on the backs of 45 hairless mice, which were then divided into vehicle-, topical tacrolimusand topical steroid-treated group. Each drug was topically applied once daily. The wound area was assessed by using dermoscopic images every two days after wounding. At 3, 7 and 11 days after wounding, 10 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Some case studies have shown that tacrolimus is effective at healing complex leg ulcers in the context of venous insufficiency or necrobiosis lipoidica when regular treatment strategies have been ineffective 41,42 . Further, a rat-based study with acute cutaneous injury demonstrated that wounds treated with topical tacrolimus versus control (petrolatum) did not differ in healing speed 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case studies have shown that tacrolimus is effective at healing complex leg ulcers in the context of venous insufficiency or necrobiosis lipoidica when regular treatment strategies have been ineffective 41,42 . Further, a rat-based study with acute cutaneous injury demonstrated that wounds treated with topical tacrolimus versus control (petrolatum) did not differ in healing speed 43 …”
Section: Resultsmentioning
confidence: 99%
“…41,42 Further, a rat-based study with acute cutaneous injury demonstrated that wounds treated with topical tacrolimus versus control (petrolatum) did not differ in healing speed. 43…”
Section: Polyclonal Antibodiesmentioning
confidence: 99%
“…Inhibiting the proliferation of fibroblasts and their tissue migration, the entire protein synthesis of tissue collagen is impaired. Following the same line of research, Nankoong et al (22) studied the effect of the topical tacrolimus therapy in the healing of cutaneous wounds in the backs of mice. They observed that after 3, 7 and 11 days of healing, there was no significant alteration in the healing of tissue between the groups under study, but the group treated with tacrolimus had slightly reduced levels of expression of mRNA of IL-1α and TGF-β.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to topical glucocorticosteroids, which seem to delay wound healing in laboratory animals, tacrolimus appears to increase epithelization, proliferation of fibroblasts and collagen synthesis, making it a good option for long-term treatment, as it does not induce atrophy either [16]. However, a comparative clinical study on the efficacy of topical tacrolimus 0.1% ointment versus triamcinolone acetonide over a follow-up period of 6 months showed no significant differences in efficacy or adverse events [15].…”
Section: Figure 2 Distribution Of Erosive Olp Cases According To Age Group and Gendermentioning
confidence: 99%